2013
DOI: 10.1111/ajt.12181
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Versus Mycophenolate Mofetil in Heart Transplantation: A Randomized, Multicenter Trial

Abstract: In an open-label, 24-month trial, 721 de novo heart transplant recipients were randomized to everolimus 1.5 mg or 3.0 mg with reduced-dose cyclosporine, or mycophenolate mofetil (MMF) 3 g/day with standarddose cyclosporine (plus corticosteroids ± induction). Primary efficacy endpoint was the 12-month composite incidence of biopsy-proven acute rejection, acute rejection associated with hemodynamic compromise, graft loss/retransplant, death or loss to follow-up. Everolimus 1.5 mg was noninferior to MMF for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
169
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(186 citation statements)
references
References 22 publications
13
169
1
3
Order By: Relevance
“…In our study, although numbers were low, there was a nonsignificant trend toward higher mGFR in the cohort of patients who remained on a CNI-free everolimus-based regimen versus those in whom low-dose CNI was reintroduced. The between-group differences are all the more striking given the relatively low trough concentrations of cyclosporine in the control arm compared with previous comparative trials of everolimus-based immunosuppression versus conventional cyclosporine therapy in heart transplant patients (9,10).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our study, although numbers were low, there was a nonsignificant trend toward higher mGFR in the cohort of patients who remained on a CNI-free everolimus-based regimen versus those in whom low-dose CNI was reintroduced. The between-group differences are all the more striking given the relatively low trough concentrations of cyclosporine in the control arm compared with previous comparative trials of everolimus-based immunosuppression versus conventional cyclosporine therapy in heart transplant patients (9,10).…”
Section: Discussionmentioning
confidence: 80%
“…Everolimus does not induce the nephrotoxicity that is associated with CNI therapy. In addition, blockade of the mTOR pathway inhibits the proliferation of fibroblasts and smooth muscle cells that characterizes cardiac allograft vasculopathy (CAV), and randomized trials have shown a reduced incidence of CAV in de novo heart transplant patients receiving everolimus (9,10). Nevertheless, the optimal time for introduction of everolimus and the relative benefit of CNI withdrawal versus ongoing lowexposure CNI therapy remain uncertain, especially with regard to long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, survival prolongation was not due to the induction of immunological tolerance, this prolongation of allograft survival seems to have a great influence on clinical organ transplantation. Considering the facts that the acute phase mortality of organ transplantation is primarily due to infectious complications (41)(42)(43), it is an attractive alternative way to reduce systemic immunosuppression with local immunosuppression of adoptive-transfer MDSCs. These strategies can be clinically applicable and might bring paramount benefits to organ transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of previous studies have demonstrated the feasibility of CNI minimization protocols with concomitant introduction of mTOR inhibitors early after HTx (7,9). However, the prospect of mTOR inhibitors introduction with early CNI elimination in de novo recipients has largely been considered unrealistic due to serious safety concerns (10,11).…”
Section: Introductionmentioning
confidence: 99%